2014
DOI: 10.1177/0192623314530533
|View full text |Cite
|
Sign up to set email alerts
|

Circulating miR-9* and miR-384-5p as Potential Indicators for Trimethyltin-induced Neurotoxicity

Abstract: Circulating microRNAs (miRNAs) show promise as biomarkers due to their tissue-specific expression and high stability. This study was conducted to investigate whether nervous system-enriched miR-9* and hippocampus-enriched miR-384-5p could be indicators of neurotoxicity in serum. Rats were given a single administration of trimethyltin (TMT) chloride at 6, 9, or 12 mg/kg by gavage, and brain and serum were collected 1, 4, and 7 days after administration. MiR-9* and miR-384-5p levels in serum and hippocampus were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 62 publications
(86 reference statements)
0
28
0
Order By: Relevance
“…Another study demonstrated that miR-384 is a promising candidate as a biomarker of spinal cord injury, because of a significant increase in miR-384 in the serum, which correlates with injury severity (Hachisuka et al, 2014). In addition, miR-384 is elevated in the hippocampus during neural cell death and is, therefore, considered to have potentially novel roles in neurotoxicity (Ogata et al, 2015) and the development of Parkinson’s disease (Jiang et al, 2016) and Alzheimer’s disease (Liu et al, 2014). In this study, we discovered another novel function of miR-384, namely a critical involvement in the development of the Th17/Treg imbalance and demyelination in the CNS during the pathogenesis of EAE through targeting of SOCS3 .…”
Section: Discussionmentioning
confidence: 99%
“…Another study demonstrated that miR-384 is a promising candidate as a biomarker of spinal cord injury, because of a significant increase in miR-384 in the serum, which correlates with injury severity (Hachisuka et al, 2014). In addition, miR-384 is elevated in the hippocampus during neural cell death and is, therefore, considered to have potentially novel roles in neurotoxicity (Ogata et al, 2015) and the development of Parkinson’s disease (Jiang et al, 2016) and Alzheimer’s disease (Liu et al, 2014). In this study, we discovered another novel function of miR-384, namely a critical involvement in the development of the Th17/Treg imbalance and demyelination in the CNS during the pathogenesis of EAE through targeting of SOCS3 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the serum level of miR-384-5p was significantly increased in mice with acute spinal cord injury and that miR-384-5p might be used as a promising biomarker for predicting the severity of acute spinal cord injury (13). In rats treated with trimethyltin, miR-384-5p was significantly upregulated with the evolution of neural cell death that was regarded as potential indicators of neurotoxicity (32). The decreased expression of miR-384-5p is required for spine enlargement associated with long-term potentiation (12).…”
Section: Discussionmentioning
confidence: 99%
“…Spinal cord injury significantly increases the expression of miR-384-5p in the serum (13). Importantly, miR-384-5p has been shown to be an indicator for trimethyltin-induced neurotoxicity (32) and is found to be differentially expressed in dopaminergic neurons following cocaine addiction (42). However, whether miR-384-5p is associated with neurotoxicity in PD remains unknown.…”
mentioning
confidence: 99%
“…By targeting the PTEN gene, mir-222 has been shown to promote neurite outgrowth (34). Additionally, mir-384 has been shown to be an indicator of neurotoxicity (35) and was found to be differentially expressed in dopaminergic neurons following cocaine addiction (36). …”
Section: Discussionmentioning
confidence: 99%